Methodological framework of cultural ecosystem service assessment - Spage, Aiga; Skujane, Daiga; Nitavska, Natalija (Landscape Architecture and Art, 2023)
In recent decades, cultural ecosystem services have been increasingly studied in the field of ecosystem services. Even more diverse studies have been conducted since the Covid-19 pandemic and today’s political situation brings cultural ecosystem services, more specifically identity, symbolic, religious and cultural-historical values even more to the fore. Although the services of cultural ecosystems in general are more and more extensively researched, mostly focusing on tourism issues, the cultural-historical, symbolic, religious and entertainment value as base not only for tourism, but also for strengthening local communities, is still rarely studied in research in the world and in Latvia due to the lack of data and the intangible nature of research. Therefore, a methodological framework for conducting such a research, selecting data from publicly available sources, as well as obtaining missing data in field studies. Also, tools for integrating results from assessment of cultural ecosystem services related to identity, religious and symbolic values into political and decision-making documents are missing. Thus, as a continuation of the study on the assessment of cultural ecosystem services and integration into political and decision-making documents, the aim of the particular article is presentation of a methodological framework developed for the assessment of cultural-historical, symbolic, religious and entertainment values in the landscape. The methodological framework includes seven steps, which are described in this article. The methodological framework created will be tested and validated in future studies, where improvements may be made depending on the situation during the process.